Salmonella kingabwa meningitis in a neonate. (28th February 2012) - Olariu, Adina; Jain, Sangita; Gupta, Ajay Kumar
Abstract : A 23-day-old male baby was admitted with 1 day history of high temperature, irritability and poor feeding. His general examination was unremarkable. Salmonella species grew from CSF culture and subsequent identification revealed Salmonella kingabwa, a serotype which rarely causes human illness. The child lived with his parents and regularly visited his grandmother for 4 h every day. Grandmother kept five snakes and five water dragons as pets. They lived in tanks and crawled freely around the house. For decades the reptiles have been known to carry Salmonella, which can be transmitted directly or indirectly to humans through ingestion of the bacteria, which causes subsequent infection. Reptile exposure is a rare but significant risk factor for Salmonella illness in England and contact with reptiles should be avoided by children less than 5 years old, pregnant ladies, older and those with impaired immunity.